Analisis Implementasi Supervisi Akademik Kepala Sekolah (Studi Kasus di SD Negeri Sitirejo) - Muhamad Ulinnuha; Slamet Utomo; Sri Utaminingsih (Jurnal Ilmiah Wahana Pendidikan, 2023)
The background of this research is the implementation of supervision activities is that are less than optimal, the principal feels that she does not master the supervision techniques or the material to be supervised, cannot make follow-up after the implementation of supervision, the principal reason is too busy, the implementation of supervision is still as it is not in accordance with the provisions that should be.The purpose of the research is to describe the academic supervision program planning, implementation, evaluation, and follow-up of academic supervision carried out by the principal of the school towards teachers.The research method used is a qualitative approach which is better known as naturalistic inquiry. In this study using a qualitative approach in the form of case study research. Techniq data collection in this research include interview techniques, observation and documentation. The data analysis technique used is a non-statistical method, namely descriptive data analysis. The technique of checking the validity of the data is done by triangulation, by means of cross-checking the data.The results of the research show that the implementation of academic supervision planning has used the technical supervision guidelines. The implementation of academic supervision still needs improvement. The principal has conducted an evaluation of academic supervision. Implementation of follow-up academic supervision has been going according to plan.The researcher concluded that the implementation of the principal's academic supervision at has been going according to plan, although it still needs improvement. Researchers suggest that the implementation of academic supervision should be carried out in a programmed, systematic and sustainable manner so that it has an impact on improving educational services